The Impact of Executive Team’s Academic Background on Corporate ESG Performance - Qi, Zhengyang (Transactions on Economics, Business and Management Research, 2024)
The ESG (Environmental, Social, and Governance) has become a significant metric for assessing a company’s long-term value and its capacity for sustainable development. This study examines the impact of executive team academic backgrounds on corporate ESG performance using data from 26,400 China’s A-share listed firms from 2008 to 2022. The findings reveal a positive correlation between the academic background of the executive team and corporate ESG performance. The enhancing effect of the executive team’s academic background on corporate ESG performance is more pronounced in firms with low auditing quality and in non-state-owned enterprises. The study provides insights for companies aiming to improve their environmental standards, fulfill social responsibilities, and enhance corporate governance.